Managing inclusion or preparing for exclusion? A critical examination of gender-responsive management of female Central and Eastern European prisoners in England and Wales - Tomaszewska, Magdalena (Punishment & society, 2023)
This article examines practitioner understandings and implementation of gender-responsive support within female prisons in England and Wales in the context of a growing emphasis on effective deportation of foreign national prisoners. Drawing on a case study of female prisoners from Central and Eastern states of the European Union (EU), we argue that the aims of gender-responsivity, designed to address women's gendered vulnerabilities to support their re-entry in the UK, are pragmatically re-shaped to accommodate the uncertainty surrounding their immigration status. We show how in practice, gender-responsive support functions at best to ‘manage’ gendered needs of women who are ‘not of interest’ to immigration authorities, and at worst to legitimate exclusion by side-lining vulnerabilities of women deemed as having ‘no right to remain’ in the UK. This occurs in the context of limited access to legal redress to challenge deportation decisions, unevenly spread resources in the female prison estate, and practitioners’ occupational cultures which emphasise paternalistic valuations of female foreign national prisoners’ femininity. We locate the findings in criminological debates about ‘gendering of borders’ and conclude with a reflection on the implications for advocacy at the time of increasingly restrictive immigration controls following the UK's exit from the EU.